Lactate levels affect motor performance in MD 1 - Caterina Tramonti; Stefania Dalise; Federica Bertolucci; Bruno Rossi; Carmelo Chisari (PAGEPress Publications, 2014)
Myotonic Dystrophy type 1 (DM1) is a dominantly inherited disease comprehending multiple features. Fatigue and exhaustion during exercise often represent significant factors able to negatively influence their compliance to rehabilitation programs. Mitochondrial abnormalities and a significant increase in oxidative markers, previously reported, suggest the hypothesis of a mitochondrial functional impairment. The study aims at evaluating oxidative metabolism efficiency in 18 DM1 patients and in 15 healthy subjects, through analysis of lactate levels at rest and after an incremental exercise test. The exercise protocol consisted of a submaximal incremental exercise performed on an electronically calibrated treadmill, maintained in predominantly aerobic condition. Lactate levels were assessed at rest and at 5, 10 and 30 minutes after the end of the exercise. The results showed early exercise-related fatigue in DM1 patients, as they performed a mean number of 9 steps, while controls completed the whole exercise. Moreover, while resting values of lactate were comparable between the patients and the control group (p=0.69), after the exercise protocol, dystrophic subjects reached higher values of lactate, at any recovery time (p<0,05). These observations suggest an early activation of anaerobic metabolism, thus evidencing an alteration in oxidative metabolism of such dystrophic patients. As far as intense aerobic training could be performed in DM1 patients, in order to improve maximal muscle oxidative capacity and blood lactate removal ability, then, this safe and validate method could be used to evaluate muscle oxidative metabolism and provide an efficient help on rehabilitation programs to be prescribed in such patients.